Experiencing good results promotes positive feelings to high-intensity exercise among young adults: A qualitative study - Kjetil L. Høydal; Eli-Karin Sjåstad Åsebø; Silje Louise Dahl (Frontiers Media S.A., 2022)
IntroductionFrom a public health perspective, it is important to gain more insight into how people can be motivated to maintain effective exercise routines. It is a common belief that moderate-intensity exercise is more pleasant and enjoyable than high-intensity training. This study aims to provide insight into (1) participants' expectations and preferences for training intensity prior to training, (2) how longer-term participation affect participants' experience of endurance training with continuous moderate-intensity training and high-intensity interval training.Materials and methodsA total of 22 participants (14 women and eight men) between the ages of 21-30 volunteered for participation. Participants were randomized and divided into two equal groups. A total of 17 participants, nine women and eight men, completed the study. One group did moderate-intensity longer-lasting training and the other did high-intensity interval training. All participants completed three training sessions per week for 8 weeks. Semi-structured interviews were conducted with each participant before and after completing the training intervention. Data was analyzed using thematic analysis. This study is a part of a larger study evaluating and comparing the effects on endurance capacity of high-intensity interval training and moderate-intensity training. Physiological data are previously published.ResultsThe results describe participants expectations prior to training, and how they experienced the actual training. The overall experience of training comprises several factors that work together. Both expectations and actual experiences (e.g., of physical pleasantness or unpleasantness, of positive or negative emotions, and of actual results from the training) contribute to the participants' overall experience of exercise.ConclusionThe major finding is that improved physical fitness was a stronger motivator than feelings of pleasantness. Experiencing good results seemed to downplay feelings of unpleasantness and reinforce positive feelings toward exercise. Lack of results reinforce negative feelings toward exercise. Participants reported high-intensity exercise as more unpleasant and exhaustive, but the interval training group were more satisfied and experienced the training as more motivating.